EARNINGS MANAGEMENT PRACTICES BEFORE AND AFTER THE IMPLEMENTATION OF PSAK 73 - Nabila Putri Ardana (GREET, 2025)
Earnings management has long been a concern for regulators and investors, as it undermines the credibility of financial reporting and distorts stakeholders’ decision-making. In Indonesia, the adoption of PSAK 73 on lease accounting, aligned with IFRS 16, represents a major regulatory reform intended to enhance transparency by eliminating opportunities for off-balance-sheet financing. This study investigates how earnings management practices evolved before and after the implementation of PSAK 73, with particular attention to managerial behavior, corporate governance, and industry-specific contexts. Using a qualitative approach, the research combines semi-structured interviews with financial managers and executives, supported by document analysis of corporate financial statements and regulatory filings. The findings reveal that prior to PSAK 73, 65% of listed firms engaged in aggressive earnings manipulation through lease classification and income smoothing, often driven by short-term performance pressures. After implementation, such practices decreased to 45%, accompanied by a decline in earnings management scores and a cultural shift toward long-term sustainability and accountability. The study highlights transparency, governance, regulatory influence, stakeholder pressure, and managerial incentives as key themes shaping corporate responses. These results contribute to the literature on accounting standards and financial ethics by demonstrating that PSAK 73 not only reduces manipulation opportunities but also fosters ethical reporting practices. The study further offers implications for regulators, auditors, and investors, while suggesting cross-country and longitudinal research for future exploration.